Resilience of Indonesian Stock Market to Fed Policy: Bibliometric Review - Muhammad Rijal Alim Rahmat; Rahmat Burhamzah (Economics and Business Journal (ECBIS), 2026)
This study conducts a bibliometric analysis of literature (2015-2025) on Indonesian stock market resilience to Federal Reserve monetary policy shocks. Data were collected from Google Scholar using Publish or Perish 8 with relevant keywords. A total of 82 publications with 476 citations (h-index = 9) were identified. VOSviewer was used for bibliometric analysis to map keyword co-occurrence in titles and abstracts. Network visualization revealed three dominant clusters: (1) Federal Reserve monetary policy and capital flow spillovers, (2) market volatility and investor behavior, and (3) financial resilience and domestic policy responses. The overlay timeline indicated a shift from spillover and volatility issues in mid-decade to resilience topics in recent years. The literature suggests that while the Indonesian stock market remains sensitive to Fed rate changes, it has shown growing resilience due to proactive domestic policy interventions